OPTIMIZING CLOUD SOLUTIONS: STREAMLINING HEALTHCARE DATA LAKES FOR COST EFFICIENCY - Santhosh Kumar Pendyala (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article explores the evolving landscape of healthcare data management and cloud cost optimization strategies. The article examines healthcare organizations' dual challenges in managing sensitive medical data while optimizing cloud infrastructure costs. It investigates the implementation of edge computing solutions, cloud-based data lakes, and advanced security frameworks in healthcare settings. The article provides detailed insights into compute resource management, cluster optimization, storage efficiency, and cost governance in healthcare cloud environments. Through analysis of real-world implementations across multiple healthcare organizations, the article demonstrates the significant impact of comprehensive cloud optimization strategies on operational efficiency, cost reduction, and data security. The findings highlight the transformative potential of modern cloud architectures in addressing the technical and financial challenges of healthcare's digital transformation.